Investigation of combining ability and superiority percentages for yield and some related traits in yellow maize using line × tester analysis - Abdel-Moneam, Maamoun A.; Sultan, M. S.; Abido, Waleed A. E.; Hadházy, Ágnes; Sadek, S. A.; Shalof, M. S. (Acta Agraria Debreceniensis, 2020)
Combining ability estimation is an important genetic attribute for maize breeders in anticipating improvement in productivity via hybridization and selection. This research was carried out to investigate the genetic structure of the 27 F1 maize hybrids established from nine lines derived from Maize Research Department and three testers, to determine general combining ability (GCA), determine crosses showing specific combining ability (SCA) and superiority percentages for crosses. Nine lines, three testers, 27 F1 hybrids and two check commercial hybrids (SC162 and SC168) were studied in randomized complete block Design (RCBD) with three replications during 2016. The results of mean squares showed that significant and highly significant for most studied traits (days to 50% tasseling, days to 50% silking, plant and ear height, ear position, ear length, no. of kernels per row, 100-kernel weight and Grain yield). Estimates of variance due to GCA and SCA and their ratio revealed predominantly non-additive gene effects for all studied traits. Lines with the best GCA effects were: P2 (line 11) and P6 (line 21) for grain yield, for testers Gm174 and Gm1021 had significant GCA effects for grain yield. The hybrids P5×Gm1021, P6×Gm1021, P7×Gm1021, P8×Gm1002, P9×Gm1002 had significant and negative SCA effects for grain yield. Crosses P1×Gm174, P2×Gm1002, P5×Gm1021, P6×Gm174, P6×Gm1021, P7×Gm1021, P8×Gm1002, P9×Gm1021 were the best combinations manifested and significant superiority percentages over than check varieties (SC162 and SC168) for most studied traits. Therefore, these hybrids may be preferred for hybrid crop development.Abbreviations: GCA general combining ability; SCA specific combining ability